Did you save some cash for a rainy COVID-19 day? The crisis and SMEs. (November 2020) - Cowling, Marc; Brown, Ross; Rocha, Augusto
As COVID-19 spreads across the globe, a common public policy response has been to enforce the temporary closure of non-essential business activity. In some countries, governments have underwritten a proportion of the wage income for staff forced to furlough or broadened their welfare systems to accommodate newly laid off workers or small business owners. While these actions are helpful, they do not explicitly address the lack of sales trading activity on business income and cash balances. In commentary, we identify what types of businesses have been increasing their cash holdings in the lead up to COVID-19 as an indication of what types of small and medium-sized enterprises (SMEs) are most at risk if the lockdown extends for a protracted period of time. We find that only 39% of the of businesses were bolstering their cash balances leading up to COVID-19 which suggests that 61% of businesses may run out of cash, including 8.6% that had no retained earnings whatsoever with micro firms at particular risk. The importance of precautionary saving for SMEs is critical to enhance resilience when Black Swan events occur.